Stakeholders’ Understandings of Human Papillomavirus (HPV) Vaccination in Sub-Saharan Africa: A Rapid Qualitative Systematic Review - Caroline Deignan; Alison Swartz; Sara Cooper; Christopher J. Colvin (Vaccines, 2021)
Cervical cancer rates in Sub-Saharan Africa (SSA) are amongst the highest worldwide. All three of the Human Papillomavirus (HPV) vaccines (9-valent, quadrivalent and bivalent HPV vaccine) provide primary protection against the most common cancer-causing strains of HPV (types 16 and 18) that are known to cause 70% of cervical cancers. Over the last five years, there has been an increase in Sub-Saharan African countries that have introduced the HPV vaccine. The majority of research has been conducted on supply-side barriers and facilitators to HPV vaccination uptake in SSA, yet little research has been conducted on demand-side or end-user perspectives of, and decisions around, HPV vaccination. In order to complement existing research, and inform current and future HPV vaccination implementation approaches, this qualitative systematic review explored Stakeholders’ understandings of HPV vaccination in SSA. This review searched the following databases: Embase (via Scopus), Scopus, MEDLINE (via PubMed), PubMed, EBSCOhost, Academic Search Premier, Africa-Wide Information, CINAHL, PsycARTICLES, PsycINFO, SocINDEX, Web of Science, and the Cochrane Controlled Register of Trials (CENTRAL) and found a total of 259 articles. Thirty-one studies were found eligible for inclusion and were analyzed thematically using Braun and Clarke’s methods for conducting a thematic analysis. The quality of included studies was assessed using the Critical Appraisal Skills Programme (CASP) checklist. Three major themes emerged from this analysis; knowledge of HPV vaccination and cervical cancer is intertwined with misinformation; fear has shaped contradictory perceptions about HPV vaccination and gender dynamics are relevant in how stakeholders understand HPV vaccination in SSA.